Nitrogen fixation in the eastern Atlantic reaches similar levels in the Southern and Northern Hemisphere. Issue 1 (27th January 2017) - Fonseca‐Batista, Debany; Dehairs, Frank; Riou, Virginie; Fripiat, François; Elskens, Marc; Deman, Florian; Brion, Natacha; Quéroué, Fabien; Bode, Maya; Auel, Holger
Abstract: Euphotic layer dinitrogen (N2 ) fixation and primary production (PP) were measured in the eastern Atlantic Ocean (38°N–21°S) using 15 N2 and 13 C bicarbonate tracer incubations. This region is influenced by Saharan dust deposition and waters with low nitrogen to phosphorus (N/P) ratios originating from the Subantarctic and the Benguela upwelling system. Depth‐integrated rates of N2 fixation in the north (0°N–38°N) ranged from 59 to 370 µmol N m −2 d −1, with the maximal value at 19°N under the influence of the northwest African upwelling. Diazotrophic activity in the south (0°S–21°S), though slightly lower, was surprisingly close to observations in the north, with values ranging from 47 to 119 µmol N m −2 d −1 . Our North Atlantic N2 fixation rates correlate well with dust deposition, while those in the South Atlantic correlate strongly with excess phosphate relative to nitrate. There, the necessary iron is assumed to be supplied from the Benguela upwelling system. When converting N2 fixation to carbon uptake using a Redfield ratio (6.6), we find that N2 fixation may support up to 9% of PP in the subtropical North Atlantic (20°N–38°N), 5% in the tropical North Atlantic (0°N–20°N), and 1% of PP in the South Atlantic (0°S–21°S). Combining our data with published data sets, we estimate an annual N input of 27.6 ± 10 Tg N yr −1 over the open Atlantic Ocean, 11% of which enters the region between 20°N and 50°N, 71% between 20°N and 10°S, and 18% between 10°N and 45°S. Plain Language Summary: During the EUROPA oceanographic expedition in the eastern Atlantic Ocean (from 38 degrees N to 21 degrees S) we studied the capacity of the micro algae communities to use dissolved N2 gas as a source of nitrogen (N) for their biosynthesis. Fourteen sites were sampled, each at four depths within the sunlit surface ocean that shelters marine algae. We carried out 24‐hour incubation experiments to measure microbial N2 fixation rates. Algae capable of fixing N2 have been shown to be stimulated where dissolved iron, a key nutrient for the N2‐fixing enzyme is abundant and where bioavaliable N is in deficit relative to phosphate based on the algal requirements. Substantial N2 fixation activities were detected in the north (0‐38 degrees N) under influence of iron‐rich dust input from the Saharan desert, with rates ranging from 59 to 370 µmol N m‐2 d‐1. N2 fixation in the southeast (0‐2 degrees S) was unexpectedly close to observations in the north, with values ranging from 47 to 119 µmol N m‐2 d‐1, in opposition to previous studies in the same region. Our findings suggest that N2 fixation in the southeast Atlantic may have been overseen and we support that this activity was likely sustained by the influence of rising deep water events, namely upwelling, in the Benguela region which convey iron‐rich waters carrying N deficit signatures. Key Points: Widespread biological N2 fixation in the eastern Atlantic Ocean between 38°N and 21°S Comparable levels in the South and North East Atlantic Reassessment of annual nitrogen input through N2 fixation in the Atlantic Ocean